2006
DOI: 10.1002/ab.20123
|View full text |Cite
|
Sign up to set email alerts
|

Aggression inhibition in high- and low-risk subjects for child physical abuse: effects of a child's hostile intent and the presence of mitigating information

Abstract: Exposure of an aggressor to the suffering of his/her victim generally inhibits subsequent attacks [e.g. Baron, 1971a] presumably because of an empathic process. Physically abusive parents and individuals at high risk for child physical abuse are thought to present a deficit in empathy [e.g. Milner, Halsey and Fultz, 1995]. The present research was designed to investigate whether highrisk, compared to low-risk, subjects for child physical abuse select more aggressive responses and aggress with more intensity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…In addition, belief in corporal punishment (Ahn, 2004 [Korean/South Korea]), more use of power assertion and less use of instructional discipline techniques (de Paúl, Asla, et al, 2006 [Spanish/Spain]), and more use of harsh discipline (Dolz, Cerezo, & Milner, 1997 [Spanish/Spain]; Montes et al, 2001 [Spanish/Spain]) were associated with elevated scores on translated versions of the Abuse scale. Similarly, more intense aggression in the presence of victim pain cues (i.e., feedback of a victim's pain level following the administration of a shock by the study participant; Pérez-Albéniz & de Paúl, 2005a [Spanish/Spain]), more aggression in the presence of mitigating information (de Paúl, Pérez-Albéniz, Ormaechea, Vergara, & de Cádiz, 2006 [Spanish/Spain]), more aggression overall (Pérez-Albéniz & de Paúl, 2005a, 2006 [Spanish/Spain]), less adaptive responses to infants' difficult behaviors (Cerezo, Trenado, & Pons-Salvador, 2006 [Spanish/Spain]), less dispositional empathy (de Paúl et al, 2008 [Spanish/Spain]; Pérez-Albéniz & de Paúl, 2003, 2004 [Spanish/Spain]), less general empathy (Pérez-Albéniz & de Paúl, 2005b [Spanish/Spain]), less empathy toward children (Pérez-Albéniz & de Paúl, 2004 [Spanish/Spain]), and less frequent use of positive parenting techniques (Dolz et al, 1997 [Spanish/Spain]) were associated with elevated scores on the Abuse scale.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, belief in corporal punishment (Ahn, 2004 [Korean/South Korea]), more use of power assertion and less use of instructional discipline techniques (de Paúl, Asla, et al, 2006 [Spanish/Spain]), and more use of harsh discipline (Dolz, Cerezo, & Milner, 1997 [Spanish/Spain]; Montes et al, 2001 [Spanish/Spain]) were associated with elevated scores on translated versions of the Abuse scale. Similarly, more intense aggression in the presence of victim pain cues (i.e., feedback of a victim's pain level following the administration of a shock by the study participant; Pérez-Albéniz & de Paúl, 2005a [Spanish/Spain]), more aggression in the presence of mitigating information (de Paúl, Pérez-Albéniz, Ormaechea, Vergara, & de Cádiz, 2006 [Spanish/Spain]), more aggression overall (Pérez-Albéniz & de Paúl, 2005a, 2006 [Spanish/Spain]), less adaptive responses to infants' difficult behaviors (Cerezo, Trenado, & Pons-Salvador, 2006 [Spanish/Spain]), less dispositional empathy (de Paúl et al, 2008 [Spanish/Spain]; Pérez-Albéniz & de Paúl, 2003, 2004 [Spanish/Spain]), less general empathy (Pérez-Albéniz & de Paúl, 2005b [Spanish/Spain]), less empathy toward children (Pérez-Albéniz & de Paúl, 2004 [Spanish/Spain]), and less frequent use of positive parenting techniques (Dolz et al, 1997 [Spanish/Spain]) were associated with elevated scores on the Abuse scale.…”
Section: Resultsmentioning
confidence: 99%
“…Child physical abuse (CPA) researchers also have used laboratory-based aggression paradigms to assess parent-to-child aggression (e.g., Bugental, Lewis, Lin, Lyon, & Kopeikin, 1999; Crouch et al, 2012; de Paúl, Pérez-Albéniz, Ormaechea, Vergara, & de Cádiz, 2006). Researchers using these paradigms engineer situations in which parents complete a task and parental aggression is inferred based on task performance.…”
Section: Why Do We Need Another Measure Of Aggressive Parenting Behav...mentioning
confidence: 99%
“…Physical maltreatment was the only type that presented an association with the maternal socio-economic status (Sneddon et al, 2010). Also, several other studies have shown that high-risk subjects for child abuse have a lower empathic capacity, and present higher anxiety and discomfort rates when observing other's discomfort, further more, they tend to act in a more aggressive and impulsive manner when faced with what they perceive as misbehavior, not taking into account mitigating information (de Paúl, Pérez-Albéniz, Ormaechea, Vergara, & de Cádiz, 2006;Pérez-Albéniz & de Paúl, 2003;Pérez-Albéniz & de Paúl, 2004).…”
Section: The Origin Of Maltreatment: An Exploratory Studymentioning
confidence: 95%